The Process of Acquiring Political Relevance of Law and Justice Elections - Budny, Michał (Political Preferences, 2023)
Political relevance is one of the most essential elements of political subjectivity. The process of its acquisition by political parties is not only a factor of their success, but also the foundation of their ability to influence the sphere of current politics. The political relevance of political parties combines both the institutional dimension of political processes and the practice of competition in three dimensions: electoral, parliamentary and cabinet. Only when parties are able to participate in all the three dimensions will they be able to perform the most important functions. The following article presents a specific dimension of acquiring political relevance, which is the management of political change.